Perancangan Komik Tentang Komunikasi Antar Pasangan Suami Istri Muda "Cinta Dalam Keluarga (Cdk)" Dan Media Promosinya - Theresia Syani Sutartoputri; Shienny Megawati Sutanto (Jurnal Vicidi, 2022)
The background of the Cinta Dalam Keluarga (CDK) comic is because there are many divorce cases in Indonesia caused by factors that affect married life and small problems that many people do not realize, one of which is communication between partners. The formulation of the CDK problem is how to design an online comic for Love in the Family (CDK) and its promotional media, to be able to provide actionable things that can be applied in communication between couples. As well as suggestions that can be taken to provide action/improve communication between partners. The research method uses primary data collection in the form of interviews with Expert Users and Extreme Users as well as surveys to Indonesian people who have used Instagram and secondary data with literature studies from books in the last 10 years and national and international journals in the last 5 years discussing comic and media design. which corresponds to the main target age 29-34 years. The result of the piloted design is that many couples understand the content, feel useful and relate to their married life. The result of designing comics and appropriate media promotions for Cinta Dalam Keluarga (CDK) is the use of storytelling in a more relaxed language and media promotion by communicating the tagline along with the topics to be discussed. Keywords: comic strip, webcomic, wedding, communication, instagram